Report to the Executive Boards of the IMF and the World Bank on the New CPSS-IOSCO Principles for Financial Market Infrastructures. (Policy Papers; Policy Paper ;, 2012)
New and revised international standards for safe and efficient Financial Market Infrastructures (FMIs) were published in April 2012. The Committee on Payment and Settlement Systems (CPSS) and the International Organization of Securities Commissions (IOSCO) reviewed the existing sets of standards for FMIs and replaced them by one new set of Principles for Financial Market Infrastructures. Appendix I outlines the 24 new Principles for FMIs as well as the 5 responsibilities for authorities. FMIs facilitate the clearing, settlement, and recording of monetary and other financial transactions, such as payments, securities and derivatives contracts. The term FMI refers to payment systems (PSs) that are systemically important, central securities depositories (CSDs), securities settlement systems (SSSs), and central counterparties (CCPs). The revised standards also incorporate additional guidance for over-the-counter (OTC) derivatives CCPs and trade repositories (TRs).